2007
DOI: 10.1074/jbc.m608741200
|View full text |Cite
|
Sign up to set email alerts
|

Actively Transcribed GAL Genes Can Be Physically Linked to the Nuclear Pore by the SAGA Chromatin Modifying Complex

Abstract: Recent work has demonstrated that some actively transcribed genes closely associate with nuclear pore complexes (NPC) at the nuclear periphery. The Saccharomyces cerevisiae Mlp1 and Mlp2 proteins are components of the inner nuclear basket of the nuclear pore that mediate interactions with these active genes. To investigate the physical link between the NPC and active loci, we identified proteins that interact with the carboxyl-terminal globular domain of Mlp1 by tandem affinity purification coupled with mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 47 publications
8
112
0
Order By: Relevance
“…In light of these findings and because of the earlier observation that the interaction of Nup2 with GAL gene promoters does not require SAGA components (Schmid et al, 2006), it is conceivable that gene repositioning to the NPC occurs mainly in two steps: the interaction of specific promoter-bound transcription activators with nucleoporins mediates the initial binding to the NPC, whereas the subsequent recruitment of SAGA might stabilize gene-NPC anchoring by interacting with TREX2 at a minimum. Moreover, chromatin immunoprecipitation (ChIP) experiments revealed that the NPCassociated protein Mlp1 binds to the UAS of active genes through direct interactions with SAGA components (Luthra et al, 2007). These data, and the fact that Mlp1 is required for efficient gene-NPC anchoring (Dieppois et al, 2006;Tan-Wong et al, 2009), suggest that -in addition to TREX2 -the interaction between Mlp1 and SAGA contributes to stabilizing gene-NPC associations during and following the early transcription activation process (Fig.…”
Section: Box 1 Schematic View Of Npc Structure and Compositionmentioning
confidence: 87%
See 1 more Smart Citation
“…In light of these findings and because of the earlier observation that the interaction of Nup2 with GAL gene promoters does not require SAGA components (Schmid et al, 2006), it is conceivable that gene repositioning to the NPC occurs mainly in two steps: the interaction of specific promoter-bound transcription activators with nucleoporins mediates the initial binding to the NPC, whereas the subsequent recruitment of SAGA might stabilize gene-NPC anchoring by interacting with TREX2 at a minimum. Moreover, chromatin immunoprecipitation (ChIP) experiments revealed that the NPCassociated protein Mlp1 binds to the UAS of active genes through direct interactions with SAGA components (Luthra et al, 2007). These data, and the fact that Mlp1 is required for efficient gene-NPC anchoring (Dieppois et al, 2006;Tan-Wong et al, 2009), suggest that -in addition to TREX2 -the interaction between Mlp1 and SAGA contributes to stabilizing gene-NPC associations during and following the early transcription activation process (Fig.…”
Section: Box 1 Schematic View Of Npc Structure and Compositionmentioning
confidence: 87%
“…In addition to the proposed tethering mediated by Nup2, genes are tethered to the NPC through interaction of the SAGA coactivator complex with the NPC-bound TREX2 complex (consisting of Sac3, Thp1, Sus1 and Cdc31) (Cabal et al, 2006;Fischer et al, 2004;Fischer et al, 2002;Rodriguez-Navarro et al, 2004). The nuclear basket Mlp proteins might also contribute to gene anchoring, as they bind the promoter of active genes through interactions with SAGA subunits (Dieppois et al, 2006;Luthra et al, 2007). The nucleoporins Nup1 and Nup60 are the docking sites of TREX2 and Mlp1, respectively (Feuerbach et al, 2002;Fischer et al, 2002).…”
Section: Box 1 Schematic View Of Npc Structure and Compositionmentioning
confidence: 99%
“…[42][43][44] Previous work has shown that components of the SAGA histone acetyltransferase complex are required for the peripheral localization of the INO1 and GAL1 genes. 21,[45][46][47] The SAGA complex has been suggested to physically associate with the nuclear pore complex through a bridging interaction between the Sac3 and Sus1 proteins. 48 Acetylation by the catalytic subunit of SAGA, the Gcn5 protein, promotes transcription initiation of the INO1 and GAL1 genes, both of which are targeted to the nuclear periphery upon activation.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Localization at the nuclear periphery correlates with an interaction of the promoters of these genes with the nuclear pore complex (NPC) 5,11 and requires nucleoporins. [12][13][14] We have focused on the mechanism by which the INO1 gene is targeted to the NPC. We find that INO1 relocalizes to the nuclear periphery rapidly, independent of mRNA production 12 and requires two DNA "zip codes" in the promoter called Gene Recruitment Sequences (GRSs 15 ) and several components of the NPC (Nup1, Nup2, Nup60, Nup157, Nup42, Gle2) and associated proteins (Mlp2, Gcn5, Spt7, Spt20, Sus1, Sac3 and Thp1).…”
Section: Introductionmentioning
confidence: 99%